Bioethanol as an alternative fuels: a review on production strategies and technique for analysis - Mohamed Ghazali, Mona Fatin Syazwanee; Mustafa, Muskhazli (Elsevier, 2025)
Bioethanol production represents an alternative source of energy that also helps minimize greenhouse gas effects. Currently, the focus of advanced technologies for bioethanol production is on the conversion of lignocellulosic biomass into renewable energy for transportation as it offers a low cost of investment and non-pollution bioprocesses. However, the utilization of lignocellulosic biomass has several challenges, including the high cost of pretreatment, the recalcitrant nature of the biomass and the requirement for robust microbes to ferment various types of sugars. Informations on the subject were achieved through a literature search using various electronic databases such as Google Scholar, ScienceDirect, Scopus, and others. From literature findings, few strategies such as separate hydrolysis and fermentation (SHF), simultaneous saccharification and fermentation (SSF), simultaneous saccharification and co-fermentation (SSCF), and consolidated bioprocessing (CBP); were found established to overcome these challenges, ultimately increasing the effectiveness of the bioconversion process and minimizing the overall cost of production. CBP was found to be the most promising strategy as direct production of ethanol from pretreated corn cob yielded 11.1 g/L ethanol without the addition of external hydrolytic catalyst. Various analytical techniques are commonly used to quantify bioethanol in a sample, and these methods were theoretically analyzed in relation to established theories. Currently, gas chromatography is known to be the most effective approach with limits of detection typically around 0.099 mg/mL, demonstrating excellent linearity and recovery rates between 91% and 109%. This paper aims to highlight the efficiency of every strategy involved in the bioconversion process and provide insights into every suitable analytical technique that can be employed to ensure the sustainability of biofuel by allowing researchers to improve the productivity and quality of bioethanol, thus promoting its role as a feasible alternative fuel.